Sport specialization, sleep, fatigue, and psychosocial ratings: do highly specialized athletes differ from their less specialized peers? - Stockbower, K. A.; Howell, D. R.; Seehusen, C. N.; Armento, A. M.; Walker, G. A. (The Physician and Sportsmedicine, 2022)
Objectives To determine if sleep quality, fatigue, anxiety, depressive symptoms, or perceptions of sport participation differ between high-, moderate-, and low-specialized high school athletes with or without prior injuries.